(3GdGYJHGQ aj GdfGSN hGdefShN aj GdMOjKs - (3eMeO Hf ehSi Hf YKeGf GHf MGRe, CHh HcQ, Rjf GdOjf, GdeYQha HGdMGRej,J (B584 (3g` s ((3CMeO Hf eMeO GdfSGN GdebQi s)
(3ChdgG (B:s
(3Chdg HYO QhGjI GdcJGH (B: (3GdMeO ddg GdcHjQ GdeJYGd GdcKjQ GdfhGd s
(3BNQgG (B:s
(3aEPG CWjY QShdg abO CWjY Gddg JYGdi HWGYI QShdg Udi Gddg Ydjg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG HYV TQhM hJYdjbGJs
(3HChdgG Jedc SfI (B887 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs